Analysis of Employees Perception and Job Satisfaction: A study of HRM practices in Post Offices - Mittal, Dr. Monika; Rattan, Dr. Meenu (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Satisfying employees at work places has ever been a crucial task before any of the organizations to ensure the success of the organization. Further, the level of job satisfaction is affected by a wide range of variables relating to individual, social, cultural, organizational and environmental factors. The present study examines the level of satisfaction of employees of post offices around the Tricity (Chandigarh, Panchkula and Mohali). The study highlights various factors determining the employees satisfaction with the job and some recommendations have also been made to enhance their satisfaction level. Data are obtained from postal assistants through structured questionnaire and used to illustrate their perception towards their organization with the help of factor analysis.